Los peregrinos urbanos en Qoyllurit’i y el juego mimético de miniaturas - Stensrud, Astrid B. (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
This article is about the pilgrims from Cusco city who participate in the miniature game in the sanctuary of Qoyllurit’i. Starting with a description of the urban socioeconomic context and the Andean ontology, this text intends to explore how we may understand the game, the meaning of the miniatures, and the importance of the pilgrimage in the contemporary urban context. A strong motivation for going to Qoyllurit’i is to empower the desires of life and ensure economic prosperity for the future through reciprocal relations with places and objects. In these relations, values like respect and faith are important. Using the analytical concepts «virtuality» and «mimesis», the article analyzes the game as a form of communication based in an ontology in which there are no distinctions between nature-culture, signifier-signified, and matter-spirit. Furthermore, it shows that indigenous religious practices are cultural and material processes which are constantly recreated in continuous and reciprocal relations between the rural and the urban. The article is based on two years and two months of ethnographic fieldwork (2001-2002, 200-2007, 2008) in a neighborhood in Cusco city and in three pilgrimages to Qoyllurit’i (2002, 2007, 2008).

Este artículo trata de los peregrinos de la ciudad de Cusco que participan en el juego de miniaturas en el santuario de Qoyllurit’i. Partiendo de una descripción del contexto socioeconómico urbano y de la ontología andina, este trabajo se propone explorar cómo podemos entender el juego, el significado de las miniaturas, y la importancia del peregrinaje en el contexto urbano contemporáneo. Una fuerte motivación para ir a Qoyllurit’i consiste en dar poder a los deseos en la vida y asegurar prosperidad económica para el futuro a través de relaciones recíprocas con lugares y objetos. En estas relaciones, valores como el respeto y la fe son importantes. Utilizando los conceptos analíticos de virtualidad y mímesis, analizo el juego como una forma de comunicación fundamentada en una ontología en la cual no se distingue entre naturaleza-cultura, materia-espíritu, significante-significado. Además, se muestra que las prácticas religiosas indígenas son procesos culturales y materiales que son recreados constantemente en relaciones continuas y recíprocas entre lo rural y lo urbano. El artículo se basa en dos años y dos meses de trabajo de campo etnográfico (2001-2002, 200-2007, 2008) en un pueblo joven de la ciudad de Cusco y en tres peregrinajes a Qoyllurit’i (2002, 2007, 2008).
The urban pilgrims in Qoyllurit’i and the mimetic miniature game
Keywords: Peregrinaje; Ontología andina; Ritual; Miniaturas; Virtualidad; Mímesis; Economía urbana; Señor de Qoyllurit’i; https://purl.org/pe-repo/ocde/ford#5.04.03